Indicators for nutrition-friendly and sustainable food systems - Nugent, Rachel; Levin, Carol; Grafton, Daniel; Fanzo, Jessica; Remans, Roseline; Anderson, C. Leigh (International Food Policy Research Institute, 2015)
As described in the preceding chapter, food systems link agriculture, environmental sustainability, and nutrition. Interest in how food systems can do more to reduce malnutrition in all its forms has increased substantially since the Global Nutrition Report 2014 was issued. The Second International Conference on Nutrition (ICN2) in November 2014, for example, focused extensively on food systems, as did a number of recent reports.